Recent understandings of gender and teachers in educational research : a review study - Kang, Daeeun (2019)
Under the era of Agenda 2030, inclusive quality education for all and gender equality are highlighted as Sustainable Development Goals (SDGs). Their interconnectedness is emphasized in corresponding targets and indicators displaying its timely relevance. Yet studies regarding gender equality in education field were conducted under specific country context. Thus, there is a need to mark the overarching understandings where each case can be positioned. This study aims to map recent understandings of gender and teachers in educational research. A review study was conducted with articles from two journals, Gender and Education and Teaching and Teacher Education. The fo-cus of analysis was in understanding what kind of gender issues have been addressed in articles on one hand and capturing the roles of teachers in the process of advancing gender equality on the other hand. The analysis was based on the concept of heteronormativity as the major challenge of gender equality. Findings of the study are two-folded. First, four themes of Feminist stance, Male talk, Intersectionality and LGBTQ emerged regarding gender issues. Second, the roles of teachers in the process of gender equality were presented. Though teachers have been impacted by heteronormativity, they can either reproduce such challenge consolidating the status quo of inequalities or exercise their agency to tackle the challenge. In this way, limits and possibilities exist at the same time. The study concludes the discussion with implications from findings regarding gender issues and teachers. Finally, the study closes leaving recommendations for future research.